2006
DOI: 10.1002/ddr.20090
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants for activated fluoropyrimidine chemotherapy

Abstract: Fluoropyrimidines (FPs) remain widely used for the treatment of diverse malignancies more than four decades following the initial report of 5-fluorouracil (5FU), the archetypal FP, as a novel compound with potential anti-neoplastic activity. Subsequent decades of research have enriched our understanding of the biochemical mechanisms that are important for FP activation as well as the genetic determinants that are predictive of the likely success, or failure, of FP chemotherapy for a particular individual. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…A potential advantage of FdUMP[10] relative to currently used FP drugs, such as 5FU, is that fewer steps of metabolic activation are required to produce FdUMP and FdUTP, the DNA-directed FP metabolites that are responsible for antitumor activity (9,22). A summary of correlation of expression of genes important for nucleotide metabolism with drug sensitivity is included in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…A potential advantage of FdUMP[10] relative to currently used FP drugs, such as 5FU, is that fewer steps of metabolic activation are required to produce FdUMP and FdUTP, the DNA-directed FP metabolites that are responsible for antitumor activity (9,22). A summary of correlation of expression of genes important for nucleotide metabolism with drug sensitivity is included in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Zn 2+ binding is energetically favored under conditions where half of the FdU are deprotonated, or slightly above physiological pH (the pK A of FdU is ∼7.6). As both Zn 2+ and FdU-containing DNA are cytotoxic toward prostate cancer cells, it is of interest whether Zn 2+ might be complexed with FdU-containing DNA for therapeutic purposes ( 16 ). In the present study, we have demonstrated that lipofectamine enhances the cytotoxicity of Zn 2+ –DNA complexes towards PCa cells.…”
Section: Discussionmentioning
confidence: 99%
“…The general cytotoxic process that cancer cells undergo in response to TS inhibitors is referred to as “thymineless death” [2, 3]. Few studies have investigated thymineless death in leukemia cells because drugs that target TS are not presently used for this indication.…”
Section: Introductionmentioning
confidence: 99%